"Are psychological attributes quantitative?" is not an empirical question: Conceptual confusions in the measurement debate. (February 2022) - Franz, David J.
Critics of psychological measurement have accused quantitative psychologists of ignoring the empirical hypothesis that psychological phenomena are quantitative (Michell), or have claimed that it is impossible in principle to find out whether psychological phenomena are actually quantitative (Trendler). By drawing on Bennett and Hacker (2003), I argue that both criticisms do not go far enough because they sidestep the fundamental conceptual problem of the measurement debate: It is impossible to give concrete formulations of the question "Are psychological attributes quantitative?" without transgressing the boundaries of meaningful language. Conceptual confusions and questionable philosophical assumptions have contributed to the misguided idea that the quantity of psychological phenomena must or can be demonstrated empirically. First, the measurement debate is characterized by misleading examples and ambiguous terminology. Second, the idea of psychological measurement is inherently Cartesian. In summary, psychological measurement is even more problematic than Michell and Trendler have argued.